2018
DOI: 10.1111/jfbc.12574
|View full text |Cite
|
Sign up to set email alerts
|

Production and immobilization of lipase PCL and its application in synthesis of α-linolenic acid-rich diacylglycerol

Abstract: α‐Linolenic acid‐rich diacylglycerol has been demonstrated with promising health promotion functions. This study examined the production, immobilization of lipase PCL, and its application in the synthesis of diacylglycerol by esterification of α‐linolenic acid with glycerol. The resin ECR8806 was selected as an effective support for the immobilization of lipase PCL. Fourier transform infrared and Laser scanning confocal microscope analysis proved that the lipase was successfully immobilized on the resin. Compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…The purification process can be a single step, multiple steps, or a combination of different techniques. Most of the literature reported on the effect of purification in increasing the DAG concentration or purity. , In some other work, characterization of purified DAG in terms of thermodynamic properties (crystallization and melting temperatures), crystal polymorphs, iodine value, fatty acid compositions, slip melting point, and solid fat content profile had been performed. , Nonetheless, a comprehensive characterization of DAG before and after purification has not been reported. It is vital to have a holistic characterization on produced DAG, especially when being applied as an emulsifier or crystallization modifier.…”
Section: Introductionmentioning
confidence: 99%
“…The purification process can be a single step, multiple steps, or a combination of different techniques. Most of the literature reported on the effect of purification in increasing the DAG concentration or purity. , In some other work, characterization of purified DAG in terms of thermodynamic properties (crystallization and melting temperatures), crystal polymorphs, iodine value, fatty acid compositions, slip melting point, and solid fat content profile had been performed. , Nonetheless, a comprehensive characterization of DAG before and after purification has not been reported. It is vital to have a holistic characterization on produced DAG, especially when being applied as an emulsifier or crystallization modifier.…”
Section: Introductionmentioning
confidence: 99%
“…These results were attributable to the higher conversion of EE and FFA to DAG through a two-step vacuum-mediated catalysis by 1,3-specific lipase ANL-MARE. Previous studies have reported that a single FFA or EE are transformed into DAG through a single reaction process ( 21 , 37 ), and FFA, as an acyl donor, has shown a higher reaction rates and conversions than EE ( 42 ). However, few studies performed one-pot conversion of the mixture substrate of EE and FFA to DAG by an enzymatic method.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al (2018) [244] immobilized lipases on electrospray fibers with some reinforcement materials such as P(GMA-co-MA)-g-PEO (poly(glycidyl methacrylate-co-methyl acrylate)-g-polyethylene oxide). It is noteworthy that the activity and stability of the derivative were improved, and consequently, the derivative became more versatile, able to be applied in various fields.…”
Section: Electrosprayingmentioning
confidence: 99%
“…Biopolymers and biocomposites are used to produce different types of lipase matrices, conjugated or not, with a broad range of ligands of distinguished properties and nature, as mentioned in recent studies: membranes, resins, nanofibers, beads, nanoparticles, nanotubes, scaffolds, colloidal particles, and nanowhiskers [203,244,298,305,308,309,312]. In the study of Elias et al (2018) [309], the biocatalyst consisting of a biopolymer carrier of nanocellulose/chitosan was prepared by extraction of nanocellulose from palm oil frond leaves, followed by consecutive crosslinking with chitosan and the Candida rugosa lipase, both using glutaraldehyde as crosslinking agent [309,320].…”
Section: Novel Carriers For Immobilizationmentioning
confidence: 99%